Efektivitas Inovasi Pembelajaran Kimia Pada Penggunaan E-Lkpd Dilengkapi Augmented Reality Berbasis Problem Based Learning - Sonelvia Utami, Chelly; Kriswantoro, Kriswantoro; Asrial, Asrial; Damris, Muhammad (Universitas Pakuan, 2025)
THE EFFECTIVENESS OF CHEMICAL LEARNING INNOVATIONS IN THE USE OF E-LKPD EQUIPPED WITH AUGMENTED REALITY BASED ON PROBLEM-BASED LEARNING This study aims to evaluate the effectiveness of chemistry learning innovation through the use of e-Student Worksheets (e-LKPD) equipped with Augmented Reality (AR) and developed based on Problem Based Learning (PBL). This innovation is implemented to help students understand abstract chemical concepts and increase their interest and involvement in the learning process. The research method used is a mixed method with data collection techniques through questionnaires, interviews and documentation. The research subjects included students and teachers at the high school level, namely SMAN 4 Jambi City who have used the e-LKPD in teaching and learning activities. The results of the analysis show that the use of e-LKPD based on AR and PBL is considered effective in supporting the learning process, indicated by increased conceptual understanding, positive student responses to the media, and active involvement in problem solving. This study shows that the integration of technology and contextual learning approaches can be an innovative alternative in developing more interesting and meaningful chemistry learning media.